Los ingresos durante la pandemia en la Ferretería “Ferreconst” del Cantón San Francisco de Puebloviejo, en el periodo 2020-2021. - Rodríguez Monserrate, Héctor John (2022)
Income is a definitely important component within all organizations or companies without exceptions, due to this it is required that the collaborator have a culture when serving the consumer, any client who buys any material is worthy of a cordial, attentive and helpful treatment. . It is very important that in any company you carefully plan those tasks that have to do with direct contact with the client. lthough many times we do not realize it, our clients are our most precious asset since thanks to them the company can survive. For this reason, every company, organization or independent professional must be clear that their strategies, actions and objectives must be totally directed towards the client since thanks to them we obtain income. The present case study was carried out with the objective of knowing and analyzing the factors that affected the income during the pandemic in the business, based on the skills of the personnel, needs, expectations, customer satisfaction, taking into account that they are the essential for the business and thus be able to achieve a favorable level of sales, and customer loyalty.